Dampak Infeksi SARS-Cov-2 Terhadap Penderita Hipertensi - Haekal Alfhad; Fitria Saftarina; Betta Kurniawan (MAJORITY, 2020)
Coronavirus disease 2019 (COVID-19) is the first viral outbreak pneumonia in Wuhan, China, in December 2019, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2). WHO reported 2.241.359 positive cases of COVID-19 patients worldwide, with a cumulative death toll of 152.551 men by April 19, 2020. As in 18 April 2020, Indonesia itself hit 6.248 positive cases with a total of 535 deaths, according to the Indonesian Health Ministry. SARS-Cov-2 is a coronaviral (β) beta group virus. In order to enter the target cell, SARS-CoV 2 uses the ACE Angiotensin conversion enzyme (ACE) 2. This can reduce the function of ACE2 which changes Angiotensin 2 into Angiotensin (1-7). The disrupted production of Angiotensin (1-7) can cause a vasodilator effect that is not optimal, so the condition of people with hypertension can be worsen. The risk of SARS-Cov-2 infection is higher among those suffering from hypertension with the drug Renin-Angiotensin-Aldosterone System inhibitor, due to the expression of ACE2. Overexpression of ACE2 may make it easier for SARS-CoV-2 to penetrate the body.